Use of time-lapse technology on fertilization verification, embryo evaluation, and utilization: A national survey in JapanAJOG Global Reports at a Glance - Mitsutoshi Yamada, MD, PhD; Kenji Ezoe, PhD; Satoshi Ueno, PhD; Osamu Yoshino, MD, PhD; Toshifumi Takahashi, MD, PhD (Elsevier, 2024)
Background: Time-lapse technology (TLT) has emerged as a significant advancement in the field of assisted reproductive technology (ART), providing continuous observation of embryos. However, limited information exists on the adoption of TLT across ART facilities and the clinical implications of its application in embryo evaluation and fertilization verification. The existing literature has not yet comprehensively examined how TLT data are utilized to optimize ART outcomes, particularly in Japan, where ART practices are highly prevalent. Objectives: This study aimed to investigate the adoption rate of TLT and its clinical effects on fertilization verification, embryo evaluation, and utilization of ART in Japan. Study Design: An online survey was conducted from December 23, 2022, to January 16, 2023, in 616 ART facilities with both email and mailed notices. The survey investigated the utilization of TLT in each facility's evaluation of oocyte morphology, fertilization, embryo culture, and morphology. Results: Overall, 345 responses were analyzed. Of these, only 42.6% confirmed fertilization at 16 to 18 hours after insemination. Most facilities defined normally fertilized eggs as 2 pronuclei (2PN; 53.3%) or a combination of a second polar body extrusion and 2PN (44.9%). Overall, 54.6% of the facilities had adopted TLT, and 76.9% to 96.9% of these facilities used TLT images for fertilization verification. At these centers, the use of 0PN embryos decreased, whereas the use of 2.1PN embryos increased. The rates of culture medium supplemented with antioxidants and hyaluronan were significantly higher in facilities with TLT than in those without TLT. TLT images were used for embryo evaluation in 94.3% of the facilities, while 31.0% used a combination of TLT images and artificial intelligence-based scoring systems. Conclusions: While TLT use is widespread in Japan, its application in evaluating fertilization and embryo development stages varies across facilities. Reaching a consensus on the optimal use of the TLT system will enhance the effectiveness, safety, and efficiency of ARTs.